2006
DOI: 10.1002/bit.20905
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of hybrid poplar to ethanol and co-products using an organosolv fractionation process: Optimization of process yields

Abstract: An organosolv process involving extraction with hot aqueous ethanol has been evaluated for bioconversion of hybrid poplar to ethanol. The process resulted in fractionation of poplar chips into a cellulose-rich solids fraction, an ethanol organosolv lignin (EOL) fraction, and a water-soluble fraction containing hemicellulosic sugars, sugar breakdown products, degraded lignin, and other components. The influence of four independent process variables (temperature, time, catalyst dose, and ethanol concentration) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
270
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(301 citation statements)
references
References 26 publications
15
270
1
4
Order By: Relevance
“…Pretreatment process may improve substrate utilization by the microbes and enhance enzyme yields 25,26 . In the present study, only native lignocellulosic substrates without pretreatment were used.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment process may improve substrate utilization by the microbes and enhance enzyme yields 25,26 . In the present study, only native lignocellulosic substrates without pretreatment were used.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in the previous paper (Kautto et al 2013), the carbohydrate recovery was assumed to be 84% based on Pan et al (2006), being considerably lower than that in the NREL study (Humbird et al 2011) (approximately 98%). Mabee et al (2006) reported a higher recovery in the organosolv cooking of softwood (90% for both glucose and hemicelluloses), suggesting that a higher carbohydrate recovery could be achievable.…”
Section: Technical Parameters Varied In Sensitivity Analysesmentioning
confidence: 96%
“…Pan et al (2006) presented how low lignin content organosolv pulps exhibit significantly better response to enzymatic hydrolysis than higher lignin content steam-exploded wood. With approximately the same enzyme loading (20.9 mg cellulase and 5.7 mg 尾-glucosidase per g cellulose) and same hydrolysis time of 36 h (but with a significantly lower solids content), Pan et al (2006) reported hybrid poplar pulp prepared at the same conditions adopted in this study to exhibit a conversion efficiency of cellulose to glucose of approximately 96%. The enzymatic conversion of organosolv-cooked hybrid poplar might therefore be higher than that of dilute acid-pretreated corn stover of the NREL study (Humbird et al 2011) (cellulose to glucose conversion of 90%).…”
Section: Technical Parameters Varied In Sensitivity Analysesmentioning
confidence: 99%
See 2 more Smart Citations